Peran Kepemimpinan dalam Meningkatkan Kualitas pada Lembaga Pendidikan Islam - Ningrum, Tika Kusuma; Firdaus, Arista Aulia; Fitria, Ida (ALSYS, 2022)
Leadership plays a key role in the direction, goals, and level of success in achieving the goals that have been set. Education is one form of organization where the level of success is largely determined by management and leadership factors. This fact shows how big the role of leadership in education is. Therefore, improvement of management and leadership systems in education is absolutely necessary. With the existence of Islamic leadership, it also provides a balance between worldly concept leadership and the concept of ukhrowi to achieve essential goals that are more than just temporary organizational goals, require a high commitment to Islamic principles and assign a place of leadership not just a humanitarian task.